Implementation of Character Education in Grade 4 Elementary School: Implementasi Pendidikan Karakter di Kelas 4 Sekolah Dasar - Dewi, Aliffia Candradewi; Rezania, Vanda (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to describe and analyze the implementation of character education in grade IV SDN Kebonsari based on 5 character values, namely religious, nationalist, integrity, independent, and mutual cooperation. This study used qualitative research methods. Data collection techniques were carried out using interviews, observation and documentation. To test the validity of the data in this study, triangulation was used. The next stage of data analysis is in the form of data reduction, data presentation and drawing conclusions. Based on the results of the study, information was obtained that the implementation of character education in grade IV SDN Kebonsari was carried out in various ways. The implementation of character education in grade IV SDN Kebonsari is implemented through habituation activities. The most prominent character values ​​in the implementation of character education are religious, nationalist, integrity, independent, and mutual cooperation.